Sistemática e filogenia do gênero Cyphoderus (Collembola, Paronellidae, Cyphoderinae) neotropicais - Oliveira, João Victor Lemos Cavalcante de (2018)
The genus Cyphoderus, distributed worldwide, was proposed by Nicolet for Entomobryomorpha without eyes, white or yellowish, with the fourth abdominal segment more than 3 times the length of the third, with scales in the body, smooth dens with piniform scales, antennal segments without subdivisions, unguis with 2 well developed basal teeth, unguiculum with a broad basal tooth. This genus has problems of classification and, in many cases, of identification due to the scarce description of diagnostic characters between species. Several authors have difficulties to classify them, having the genus been treated as belonging to different families. Recently, chaetotaxy has been added to the descriptions of new species and more rarely molecular information. However, in this work we aim to review the Neotropical species of the genus Cyphoderus, to establish hypotheses of primary homology for the analysis of parsimony and to propose a hypothesis of phylogeny for the genus Cyphoderus Neotropical. The phylogenetic analysis of the genus was carried out with morphological data to test the monophyletic and if the clusters based on the mucro form, proposed by Delamare-Deboutteville, make up groups of natural species. The results indicate that the genus Cyphoderus is monophyletic, more closely related to Paronellidae than Lepidocyrtinae or Entomobryidae and that the group proposed by Delamare-Deboutteville, apparently, is artificial, helping only for species identification.